PORTRAITS D’UN IMAGINAIRE DE L’AVANT-GARDE : LE CARRÉ NOIR SUR FOND BLANC DE KAZIMIR MALEVITCH ET SES RÉINCARNATIONS ARTISTIQUES (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
Kazimir Malevitch’s “Black Square” (1915) is one of the most recycled paintings in recent art history. More or less successfully, respectfully or ironically, artists from all around have gleefully reproduced it, ridiculed it, embezzled it and recycled it. In Russia, such has been the gravity of this phenomenon for the last thirty years, so that, it led to contemporary Russian art not being perceived as derived from Malevitch but on Malevitch. By retracing the long and tumultuous history of “Black Square” and its numerous artistic ‘reincarnations,’ this essay focuses on what these practices of reproduction tell us about the attitude of artists towards “Black Square” itself but also, perhaps mainly, about their relationship to an avant-garde with a controversial heritage of which this painting became the icon.